Intelligent System using the concept of Group Profiling by hybrid User Profiling (International Journal of Current Engineering and Technology, 2014)
Many researchers have been done in this field. We propose a system which uses aggregation-based group profiling methods to form group profile using the users’ profile by hybrid method and applying this concept to group profile and gaining the benefits of group profile. The performance of the system is calculated by the user satisfaction level. The system can applied to existing system to improve the performance for providing personalized information. The results shows gain in satisfaction level by comparing with recommendation given by hybrid user profile.
Keywords: Aggregation, text mining, user profiling, group profiling.